Analisis Pengaruh Inflansi, BI Rate, Kurs Valuta Asing Dan Return On Equity (ROE) Terhadap Harga Saham Pada Bank BUMN Yang Terdaftar Di BEI - Indriyani Sulistiyanti; M. Rimawan; Nurul Huda (Indo Publishing, 2025)
The purpose of this study is to analyze the effect of inflation, BI rate, foreign exchange rates and return on equity (ROE) on stock prices in state-owned banks listed on the IDX. This research was conducted on the Indonesia Stock Exchange (IDX) with the object used being state-owned banks. This research is an associative quantitative study. The type of data used in this study is data with research instruments in the form of a list of tables consisting of balance sheet and income statement data in the form of inflation data, BI rate, foreign exchange rates, net profit, total equity and stock prices for 5 years, namely from 2019 to 2023. The population in this study were all state-owned banks listed on the IDX from 2019-2023, namely 5 banks. The sample in this study was 4 state-owned banks listed on the IDX from 2019-2023. The sampling technique used was purposive sampling. The data collection technique used in this study was documentation and literature study techniques. Documentation data collection technique is a method used to obtain data. The data analysis techniques used are classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results of the study indicate that Inflation, BI Rate, Foreign Exchange Rate and Return On Equity (ROE) have a simultaneous effect on Stock Prices in state-owned banks listed on the IDX.